Nonimmune hydrops foetalis: value of perinatal autopsy and placental examination in determining aetiology - T., Ramya; G., Umamaheswari; V., Chaitra (International Journal of Research in Medical Sciences, 2018)
Background: Authors sought to determine the possible factors in the causation of nonimmune hydrops foetalis by perinatal autopsy with placental examination and to reduce the number of cases in which the cause remains elusive. Methods: Twenty five cases of nonimmune hydrops foetalis were identified in about 200 consecutive perinatal autopsies (including placental examination) performed during a 11 year period. The results were correlated with clinical, laboratory and imaging characteristics in an attempt to establish the aetiology. Results: Perinatal autopsy and placental examination confirmed the following aetiologies: cardiovascular causes (8) [isolated (4), syndromic (3) and associated chromosomal (1)], placental causes (5), chromosomal (4) [isolated(3) and associated cardiovascular disease (1)], intrathoracic (3), genitourinary causes (3), infections(1),gastrointestinal lesions (1) and idiopathic causes (1). Placental mesenchymal dysplasia was a unique pathology identified among the placental lesions, which constituted the second most common cause of nonimmune hydrops foetalis. Despite careful examination no cause was identified in one case. In more than 50% of studied cases, autopsy examination either refuted or altered the ultrasound diagnosis completely. Conclusions: The perinatal autopsy in combination with placental study and prenatal imaging represents the most promising tool in the evaluation of aetiology of nonimmune hydrops foetalis. The identification of a cause for nonimmune hydrops foetalis will provide a better correlation with recurrence risk and parental counselling.